Haematological and Biochemical Profile of Balb-c Mice - Barbosa, Brenna de Sousa; Praxedes, Érika Almeida; Lima, Mikael Almeida; Pimentel, Muriel Magda Lustosa; Santos, Fernanda Araujo; Brito, Parmênedes Dias; Lelis, Ivana Cristina Nunes Gadelha; Macedo, Michelly Fernandes de; Bezerra, Marcelo Barbosa (Acta Scientiae Veterinariae, 2017)
Background: Animal models are widely used in scientific research because of the ability to generate information from an organism like everything under a given experimental condition. Hematological and biochemical tests in laboratory animals are essential for the validation of several scientific studies. In addition, it standardizes physiological values for these animals according to their sex, age, lineage, environment, and nutritional status. The present work aims to establish reference values for biochemical and hematological standards in Balb/c mice, for males and females. Materials, Methods & Results: A total of 50 male and female mice were used at reproductive age. The procedures for collecting, processing, and analyzing the samples were standardized. The collected blood samples were immediately transferred to eppendorf tubes containing heparin, and intended for hematological and biochemical evaluation. The hematological evaluation consisted of Red blood cell count (RBC), Leukocyte counts (WBC), Platelet counts (PLT), Hematocrit (HCT), Hemoglobin concentration (HGB), Mean corpuscular volume (MCV), and Mean corpuscular hemoglobin concentration (MCHC). Already the quantified biochemical parameters were: urea, creatinine, alanina aminotransaminase (ALT), aspartato aminotransaminase (AST) and fosfatase alcalina (FAL). The differential leukocyte count was also performed. Hematological results obtained for males and females were: 9.19 ± 3.35 (106/mm³) and 7.3 ± 2.01(106/mm³) of RBC; 35.8 ± 6.7% and 38.44 ± 3.93% of HCT; 11.51 ± 2.17 g/dL and 11.85 ± 1.56 g/dL of HGB; 45.83 ± 15.03 fL and 60.26 ± 18.25 fL of VCM; 31.80 ± 1.15% and 31.88 ± 0.99% of MCHC; and, 5380 ± 1994.21(10³/mm³) and 3564 ± 1071(10³/mm³) of WBC. The platelet counts were 878.92 ± 84.19 and 678.28 ± 227.21, for males and females respectively. And for differential leukocyte counts, for males and females: eosinophils 2.12 ± 1.09% and 2.16 ± 1.71%; monocytes 2.84 ± 1.03% and 2.68 ± 1%; lymphocytes 68 ± 8.36% and 71.76 ± 5.9%; neutrophils 27.04 ± 8.55% and 22.96 ± 5.54%. Basophils were not quantified in the samples. As for the biochemical parameters, values of 54.16 ± 27.8 UI/L and 29.72 ± 4.4 UI/L of ALT; 89.56 ± 47.73 UI/L and 71.32 ± 8.12 UI/L of AST; 3.76 ± 2.08 UI/L and 2.32 ± 0.85 UI/L of FAL; 31.76 ± 21.08 mg/dL and 41.48 ± 13.61 mg/dL of urea; and 0.76 ± 0.18 mg/dL and 0.44 ± 0.11 mg/dL of creatinine. Discussion: The mean corpuscular volume, mean corpuscular hemoglobin concentration, leukocyte, and platelet counts diverged from those found in literature. For the biochemical values, it was observed that creatinine values were different from those exhibited by other authors. Such divergences might be explained by the activity of endocrine organs, such as the production and/or release of activation/differentiation factors, and stress, applied methodology, lineage, or individual variability. In addition, differences in the methodologies applied may be responsible for variations in hematological and biochemical values, requiring the standardization of the equipment and reagents used, as well as the adoption of a range that represents the minimum and maximum values within the normal physiological standard for given mouse lineage. In conclusion, the values presented in the present work are within the variation curve for rodents, and can be used as reference for other studies that use these animals.